2013
DOI: 10.1200/jco.2012.46.3299
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin and Radiotherapy With or Without Erlotinib in Locally Advanced Squamous Cell Carcinoma of the Head and Neck: A Randomized Phase II Trial

Abstract: Erlotinib did not increase the toxicity of cisplatin and radiotherapy in patients with locally advanced HNSCC but failed to significantly increase CRR or PFS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 176 publications
(102 citation statements)
references
References 21 publications
(9 reference statements)
4
96
0
2
Order By: Relevance
“…Previous models relied on a single injection of high-dose cisplatin, resulting in high toxicity and little reduction in hearing sensitivity (8)(9)(10). We developed a new mouse model of cisplatin ototoxicity that approximates the pattern of multiple cycles of cisplatin administration in humans (11)(12)(13). We evaluated two cisplatin administration protocols.…”
Section: Resultsmentioning
confidence: 99%
“…Previous models relied on a single injection of high-dose cisplatin, resulting in high toxicity and little reduction in hearing sensitivity (8)(9)(10). We developed a new mouse model of cisplatin ototoxicity that approximates the pattern of multiple cycles of cisplatin administration in humans (11)(12)(13). We evaluated two cisplatin administration protocols.…”
Section: Resultsmentioning
confidence: 99%
“…SCCs do not commonly harbor somatic oncogene-activating mutations, but instead are associated with frequent mutational inactivation of tumor suppressor pathways including p53 and NOTCH, the therapeutic implications of which remain to be established (2,3). In addition, although the EGFR is an attractive therapeutic target that is overexpressed or amplified in a subset of cases, only limited success with EGFR-directed therapy has been achieved in SCC despite intensive efforts over many years (4,5). Recent systematic sequencing studies of HNSCC have confirmed the remarkable rarity of tumor-associated somatic mutations in well-established oncogenic drivers, which include HRAS (4% of cases) and the PI3K catalytic subunit PIK3CA (7% of cases) (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Targeting the EGFR by tyrosine kinase inhibitors is another well-studied field of oncology, particularly in the case of EGFR-mutated non-small cell lung cancer (NSCLC), in which erlotinib and gefitinib serve as useful drugs that aid the improvement of progression-free survival and overall survival (19). Unfortunately, in an unselected cohort of head and neck cancer patients, erlotinib failed to improve progression-free survival when used in combination with cisplatin and radiotherapy (20). The role of erlotinib in head and neck cancer may be more efficacious in the field of chemoprevention.…”
Section: Introductionmentioning
confidence: 99%